Web-Based File Clustering and Indexing for Mindoro State University - Luzon, Christine A.; Lacatan, Luisito L.; Bangalisan, Harold Y.; Osapdin, Jayvee M. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – The Web-Based File Clustering and Indexing for Mindoro State University aim to organize data circulated over the Web into groups/collections to facilitate data availability and access, and at the same time meet user preferences.  The main beneﬁts include: increasing Web information accessibility, understanding users’ navigation behavior, improving information retrieval and content delivery on the Web. Web-based file clustering could help in reaching the required documents that the user is searching for. Method – In this paper a novel approach has been introduced for search results clustering that is based on the semantics of the retrieved documents rather than the syntax of the terms in those documents. Data clustering was used to improve the information retrieval from the collection of documents. Data were processed and analyzed using SPSS (version 18) where the instrument was evaluated to test the reliability and validity of the measures used. Evaluation was based on a Likert scale of Excellent, Good, Fair, and Poor as described for the selected quality characteristics. Results – A total of 200 questionnaires were distributed with a return rate of 100%. The questionnaire was tested 0.735 using Cronbach’s Alpha Coefficient and considered a reliable instrument. Four quality characteristics were evaluated in this study; Usability, Performance Efficiency, Reliability, and Functionality Suitability. Conclusion - The Web-based file clustering could help in reaching the required documents that the user is searching for.  The need for an information retrieval mechanism can only be supported if the document collection is organized into a meaningful structure, which allows part or all the document collection to be browsed at each stage of a search. Recommendations – It is recommended that upon uploading of file it will show the use of the file and where it is originated (department). It is also recommended to create an index to cluster not only the file type but also the content and use of a file. Explore the clustering to a wider scope. Practical Implications – Document clustering provides a structure for organizing large bodies of text for efficient browsing and searching and helps a lot for the Mindoro State University for records/ document processing. Indexing is the best tool to maintain uniqueness of records in a database. Whenever new files or records are created, it can be easily added to the index. This makes it easy to keep documents up-to-date at all times. Grouping documents into two or more categories improves search time and makes life easier for everyone.